Active Learning to Improve Student Learning Experiences in an Online Postgraduate Course - Lamon, Séverine; Knowles, Olivia; Hendy, Ashlee; Story, Ian; Currey, Judy (Frontiers in Education, 2020)
Post-graduate programs attract older students, who often work part-time or full-time and have child-care responsibilities. In the Information Age, online learning environments can help these students to meet their learning objectives more efficiently and provide a unique opportunity to address individual learning preferences. The aim of this study was to assess the learning experiences of postgraduate students in an online learning environment delivering content in a guided, self-directed way focusing on active learning opportunities. Two-hundred and eighty-seven students participated in the study. A pragmatic descriptive design with purposive sampling was used to examine the impact of a newly developed active online learning environment on student commitment, performance and satisfaction when compared to a passive, pre-recorded lecture. In contrast to our hypothesis that all metrics would improve with subject redevelopment, student performance and commitment did not improve in the active online learning environment; however, student satisfaction increased significantly. These findings might be partly attributed to the increased cognitive load associated to online learning. This study demonstrates how, for postgraduate students choosing online learning, active learning experiences can be used to provide students with a greater sense of satisfaction while acknowledging for the heterogeneity of the cohort and its different learning preferences. However, in the worldwide context of remote learning rapidly and urgently expanding, it also outlines that online learning needs to be carefully scaffolded to ensure deep learning and that the impact of the transition to online learning on performance and commitment should be carefully considered, especially when directed at non-experienced students.